Evaluation and Mapping of Sustainable Water and Wastewater Treatment with Membrane Processes in South Africa and Sweden - Heidi Richards; Frank Lipnizki (The Thinker)
Membrane technology is crucial to achieving Sustainable Development Goal No. 6 of clean water and sanitation for all. Despite its numerous benefits, high capital and operating costs pose major challenges. Recent research has focused on sustainable materials as membranes and more effective cleaning regimes to reduce costs and improve membrane lifespan. While South Africa and Sweden have both begun using membrane technology for water and wastewater treatment, it remains relatively rare. Collaborations through SASUF aim to evaluate and share best practices. Although MBRs have produced high-quality effluent in South Africa, cost, maintenance, and membrane replacement, as well as river pollution, remain major considerations. In contrast, Sweden has seen large-scale membrane installations in drinking water and wastewater treatment plants. Establishing working membrane references is crucial to the success of membrane technology, which is well-established globally but often requires local adaptations. Collaborations between the two countries are essential to support this approach by sharing knowledge and learning from each other.